Low-dose irradiation programs macrophage differentiation to an iNOS+/M1 phenotype that orchestrates effective T cell immunotherapy - Klug, Felix; Prakash, Hridayesh; Huber, Peter E.; Seibel, Tobias Julian; Bender, Noemi; Halama, Niels; Pfirschke, Christina; Voß, Ralf-Holger; Timke, Carmen; Umansky, Ludmila; Klapproth, Kay; Schäkel, Knut; et al. (Cancer cell, 2013)
Inefficient T cell migration is a major limitation of cancer immunotherapy. Targeted activation of the tumor microenvironment may overcome this barrier. We demonstrate that neoadjuvant local low-dose gamma irradiation (LDI) causes normalization of aberrant vasculature and efficient recruitment of tumor-specific T cells in human pancreatic carcinomas and T-cell-mediated tumor rejection and prolonged survival in otherwise immune refractory spontaneous and xenotransplant mouse tumor models. LDI (local or pre-adoptive-transfer) programs the differentiation of iNOS+ M1 macrophages that orchestrate CTL recruitment into and killing within solid tumors through iNOS by inducing endothelial activation and the expression of TH1 chemokines and by suppressing the production of angiogenic, immunosuppressive, and tumor growth factors.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 08.06.2022